Takallam: An Android Application to Enhance Literacy of Arabic Expression - Ummi Azizah Rachmawati; Aya Yahya; Puspa Setia Pratiwi; Sri Puji Utami; Febri Ufaira Hasan; Rama Abirami K. (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2024)
The Arabic language holds great significance in Islamic culture. Arabic is traditionally learned through in-person instruction in classrooms or scientific gatherings, while another method involves memorizing words from books or dictionaries. However, this memorization technique is often less effective due to the repetitive reading required. An alternative approach to learning Arabic is through information system media. In this research, the researchers developed a multimedia application to facilitate learning basic Arabic conversations. The research follows the Prototyping methodology, which involves building and refining a system model. This process includes seven steps: collecting requirements, developing prototypes, evaluating prototypes, coding, testing, system evaluation, and implementation. The Android-based mobile application, developed using Android Studio, incorporates multimedia features. The outcome of this research is the development of the Takallam app, designed to help users learn basic Arabic conversation. Takallam includes interactive dialogues, practical phrases, and engaging quizzes, with cartoon animations to enhance the learning experience and make practice more enjoyable. The System Usability Scale test yielded an average score of 74, and Beta Testing showed an 80% feasibility rate, confirming that the application meets the required criteria.